Diurnal variation in tennis service - Atkinson, G.; Speirs, L. (Perceptual and Motor Skills, 1998)
With informed consent, 6 competitive tennis players performed alternate 15 "first" (emphasis-speed) serves and 15 "second" (emphasis-accuracy) serves at 09:00, 14:00 and 18:00 hours. Serve velocity was measured by the digitisation of video footage of each serve. The Hewitt Tennis Achievement Test was employed to measure the accuracy of serve. The amount of spin imparted on the ball was not measured. First serves were at all times of day faster than second serves. First serves were faster but least accurate at 18:00 hours, the time of day that body temperature and grip strength were highest. At 09:00 hours, first serves were just as accurate as second serves, even though velocity of first serves was higher. No effects for time of day were found for the speed and accuracy of second serves. These results indicate that time of day does affect the performance of tennis serves in a way that suggest a nonlinear relationship between velocity and accuracy.